PENTINGNYA PENDIDIKAN KEJURUAN BERORIENTASI PASAR TENAGA KERJA - Sutiyatno, Sukris (Edukasi: Jurnal Penelitian dan Artikel Pendidikan, 2010)
The role of work based learning is very important for providing qualified labors needed by industry. A central argument in favor of work-based learning is that students acquire various practical skills and that they learn about industries and careers. After graduating from vocational education, the students are ready to enter the labor market so that the vocational school should design the curriculum which is relevant with the demand of labor market.